Fortification methods of coenzyme Q10 in yogurt and its health functionality—a review - Shaswati Sarma; Shiny Derose; Nagamaniammai Govindarajan; Musthafa Mohamed Essa; M. Walid Qoronfleh; Saravana Babu Chidambaram; Buthaina Al-Bulushi (Frontiers in Bioscience-Scholar, 2021)
Coenzyme Q10 (CoQ10) is an antioxidant, fat-soluble component present in the mitochondrial cells. It provides beneficial results in the treatment of male infertility. In the current scenario, the sedative lifestyle, diet and stress in human lead to excessive free radicals (ROS), leading to health aliments. The review is conducted to compare the effect of different fortification methods of CoQ10 in the Yogurt. The study showed that nanoparticles form of CoQ10 in yogurt showed higher bioaccesiblity rates in humans, and the microencapsulation of CoQ10 showed a low amount of Ubiquinone released during its shelf life. The functional Yogurt produced by the Monascus-fermented soybean powder (MFSP) co-fermentation has been shown to have high free radicals scavenging activity. Thus, the review observes that each fortified sample is useful in its way as CoQ10 supplements. Further studies must be done for accurate conclusions on its effect on male infertility, and other fortification media can be explored.